Improved diagnostic yield of neuromuscular disorders applying clinical exome sequencing in patients arising from a consanguineous population. Issue 3 (21st July 2016) - Fattahi, Z.; Kalhor, Z.; Fadaee, M.; Vazehan, R.; Parsimehr, E.; Abolhassani, A.; Beheshtian, M.; Zamani, G.; Nafissi, S.; Nilipour, Y.; Akbari, M.R.; Kahrizi, K.; et al.
Abstract : Neuromuscular diseases (NMDs) include a broad range of disorders affecting muscles, nerves and neuromuscular junctions. Their overlapping phenotypes and heterogeneous genetic nature have created challenges in diagnosis which calls for the implementation of massive parallel sequencing as a candidate strategy to increase the diagnostic yield. In this study, total of 45 patients, mostly offspring of consanguineous marriages were examined using whole exome sequencing. Data analysis was performed to identify the most probable pathogenic rare variants in known NMD genes which led to identification of causal variants for 33 out of 45 patients (73.3%) in the following known genes: CAPN3, Col6A1, Col6A3, DMD, DYSF, FHL1, GJB1, ISPD, LAMA2, LMNA, PLEC1, RYR1, SGCA, SGCB, SYNE1, TNNT1 and 22 novel pathogenic variants were detected. Today, the advantage of whole exome sequencing in clinical diagnostic strategies of heterogeneous disorders is clear. In this cohort, a diagnostic yield of 73.3% was achieved which is quite high compared to the overall reported diagnostic yield of 25% to 50%. This could be explained by the consanguineous background of these patients and is another strong advantage of offering clinical exome sequencing in diagnostic laboratories, especially in populations with high rate of consanguinity. Abstract : Study Flowchart.